2017
DOI: 10.1111/jth.13706
|View full text |Cite
|
Sign up to set email alerts
|

The recommended dose of idarucizumab may not always be sufficient for sustained reversal of dabigatran

Abstract: Idarucizumab is a monoclonal antibody fragment designed for reversing the anticoagulant effects of dabigatran. Administration is recommended as two intravenous boluses of 2.5 g within 15 min of each other or as a single 5 g bolus. However, in certain situations a second dose of the drug could be necessary. We report the case of a 77-year-old man, treated with dabigatran for paroxysmal atrial fibrillation. He presented at our department with acute renal failure, concomitant massive dabigatran accumulation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 17 publications
1
40
0
3
Order By: Relevance
“…Although TT/APTT is often used as a surrogate marker of dabigatran anticoagulant effect, we were unable to assess the association between renal impairment and definite dabigatran rebound due to an insufficient number of patients with dabigatran level measurements, despite the test’s availability at our central laboratory. Nevertheless, our results support the observation that patients with chronic or acute kidney injury are at an increased risk of experiencing a dabigatran rebound . The dabigatran rebound is thought to occur as a result of redistribution of unbound dabigatran from the extravascular to the intravascular compartment .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although TT/APTT is often used as a surrogate marker of dabigatran anticoagulant effect, we were unable to assess the association between renal impairment and definite dabigatran rebound due to an insufficient number of patients with dabigatran level measurements, despite the test’s availability at our central laboratory. Nevertheless, our results support the observation that patients with chronic or acute kidney injury are at an increased risk of experiencing a dabigatran rebound . The dabigatran rebound is thought to occur as a result of redistribution of unbound dabigatran from the extravascular to the intravascular compartment .…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, our results support the observation that patients with chronic or acute kidney injury are at an increased risk of experiencing a dabigatran rebound. 10,11 The dabigatran rebound is thought to occur as a result of redistribution of unbound dabigatran from the extravascular to the intravascular compartment. 9 It is plausible that patients with renal failure and, consequently, higher plasma dabigatran levels have increased extravascular concentrations of dabigatran that is redistributed back into the intravascular compartment over time.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients experienced a rise in unbound dabigatran levels around 24 hours following the dose of idarucizumab which may be related to redistribution of dabigatran from the extravascular compartment. There have been a few isolated reports of incomplete dabigatran reversal using the standard 5 g idarucizumab dosing in the setting of severe renal failure . There may be a role for repeated doses idarucizumab in these situations, as well as hemodialysis for dabigatran reversal …”
Section: Dabigatran Reversalmentioning
confidence: 99%
“…I read with interest the case report by Simon et al . published in a recent issue of this journal, and I wish to make some comments.…”
mentioning
confidence: 99%
“…The patient reported by Simon et al . was taking dabigatran, and received idarucizumab for immediate reversal of anticoagulation. Measurement of the dabigatran concentration showed that the antidote administration was successful, but, after a few hours, there was a rebound in the plasma level of dabigatran that was greater than expected based on previous reports .…”
mentioning
confidence: 99%